2016
DOI: 10.1007/s00404-016-4226-3
|View full text |Cite
|
Sign up to set email alerts
|

The sL1CAM in sera of patients with endometrial and ovarian cancers

Abstract: PurposeL1CAM is a cell adhesion molecule suspected to play an important role in carcinogenesis. The objective of the study was to evaluate the level of soluble L1CAM in the sera of patients with endometrial and ovarian carcinomas and verify the feasibility of the sL1CAM as a marker of these carcinomas.Methods35 endometrial and 18 ovarian cancer patients were enrolled in the study. 43 patients with benign gynecological conditions constituted a control group. The sL1CAM serum level was measured with ELISA test i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
6
2
Order By: Relevance
“…Our results are consistent with the previous study published by Wojciechowski et al (n = 35). Although the authors observed different L1CAM serum levels in EC patients compared to individuals with benign gynecological conditions, they were unable to demonstrate correlation among L1CAM serum levels and stage, histological type or tumor grading [19]. On the contrary, we did not confirm the correlation of L1CAM serum levels with the lymph node involvement demonstrated by Tangen et al (n = 372; p = 0.048) [20].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our results are consistent with the previous study published by Wojciechowski et al (n = 35). Although the authors observed different L1CAM serum levels in EC patients compared to individuals with benign gynecological conditions, they were unable to demonstrate correlation among L1CAM serum levels and stage, histological type or tumor grading [19]. On the contrary, we did not confirm the correlation of L1CAM serum levels with the lymph node involvement demonstrated by Tangen et al (n = 372; p = 0.048) [20].…”
Section: Discussioncontrasting
confidence: 85%
“…L1CAM overexpression in EC tissues represents a negative prognostic marker, signaling both more aggressive behavior of the tumor and shorter survival of patients [17,18]. The significance of L1CAM serum level measurement has not been unambiguously established yet [19,20]. All studies concerning circulating DJ1 and L1CAM serum levels assessed merely one-time sampling events without studying the potential significance of time-dependent changes in serial DJ1 or L1CAM serum levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Fogel et al (2003 ), 9 out of 10 patients with L1CAM-positive endometrial tumours also had detectable concentrations of sL1CAM in preoperative serum samples. A recent study investigating serum levels of sL1CAM in 35 endometrial cancer patients found it to be lower in patients compared with healthy controls, and no correlations between soluble L1CAM concentration and histopathology, stage or grade were found ( Wojciechowski et al , 2017 ). The latter is contradictory to our results as we find that the level of sL1CAM is significantly increased in endometrial cancer patients compared with healthy controls, and that a high level of sL1CAM is associated with aggressive disease characteristics and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soluble L1CAM (sL1CAM) is suggested to be a valuable circulating biomarker in different cancers ( Zander et al , 2011 ; Bondong et al , 2012 ). It has been detected in the culture medium from different cell lines including melanoma, breast and ovarian cancer ( Beer et al , 1999 ; Gutwein et al , 2005 ; Li and Galileo, 2010 ), and also in serum and ascites of endometrial and ovarian cancer ( Fogel et al , 2003 ; Wojciechowski et al , 2017 ), suggesting that the soluble form of L1CAM may also play a role in these cancers.…”
mentioning
confidence: 99%
“…Other studies also showed that sL1 levels correlated significantly with disease stage, progression, and recurrence in ovarian cancer and GIST patients. 41,43,44 It is not clear why higher sL1 levels predict for poor outcomes in BC and other types of cancer. Heiz et al 12 found that the release of sL1 from the renal carcinoma cell surface did not lead to L1-CAM downregulation but more likely served as a method to produce sL1.…”
Section: Jun-dong Wu Et Almentioning
confidence: 99%